Analisis Tingkat Pencemaran PM₁₀ Akibat Aktivitas Kendaraan Bermotor: (Studi Kasus Jalan Cristina Martha Tiahahu Kota Kendari) - Nurhaliza, Siti; Assiddieq, Moch.; Sumarlin, Sumarlin (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2025)
The volume of motor vehicles on Christina Martha Tiahahu Street is quite high, especially on weekdays (Monday) with 21,364 vehicles at point one and 14,484 vehicles at point two, while the lowest vehicle volume was on Thursday with 17,882 vehicles at point one and 12,227 vehicles at point two. The most dominant vehicle category is motorcycles. The results obtained indicate that the high vehicle density has both positive and negative impacts. The positive impact is an increase in income or the financial well-being of residents around Christina Martha Tiahahu Street, while the negative impact is air pollution caused by the high volume of vehicles, and prolonged exposure to dust in the air can lead to respiratory issues in humans. Based on the measurements taken, the concentration of Particulate Matter 10 (PM10) is still below the ambient air quality standard threshold, so the potential impact on health is considered low. However, the excessive exposure to PM10 from ambient air, even if below the threshold limit, still has the potential to trigger acute respiratory infection (ARI) incidents, reaching 87.95%. In certain conditions, such exposure can even lead to death.